The physics of clinical MR taught through images - Runge, Val M.; Nitz, Wolfgang R., 1953-; Heverhagen, Johannes T. (Thieme Publishers New York, 2018)
"To make optimal use of MRI technology, radiologists need an understanding of MRI physics. This can be a difficult area to master for radiologists, and it becomes increasingly challenging as new MRI techniques and new software programs are introduced. While most MRI physics books and chapters are filled with dense text and equations, Runge's book takes a very reader-friendly and practice-oriented approach, leading with images and presenting clear, concise text on understanding MRI physics and on using these principles to acquire optimal MRI Images and interpret results. The new edition text and images are extensively revised to reflect developments in the field, and there are 12 new chapters"--Provided by publisher